Holographic projection with an extended depth of focus for highly tilted screens. (March 2022) - Makowski, Michał; Shimobaba, Tomoyoshi; Kowalczyk, Adam; Sypek, Maciej; Starobrat, Joanna; Suszek, Jarosław; Sobczyk, Artur; Kolodziejczyk, Andrzej
Highlights: High quality holographic projection on a highly tilted screen. Extended depth of focus of projection with static phase masks. Anamorphic lossless magnification of projected image to 16:9 aspect ratio. Effective increase of diffraction angles of a spatial light modulator. Abstract: Although holographic projection is still gaining its momentum, it will most likely be realized as short-throw projection on highly tilted screens. This will require the depth of focus significantly larger than the native one coming from the f-number of the optical setup. Here we present a simple and lossless method of extending the depth of focus by a modified holographic encoding comprising virtual optical elements, allowing sharp imaging on a screen tilted by 56°. Numerical simulations and experimental validations on a spatial light modulator are given. The experiment proved the increase of field depth which barely compromises the image quality and its brightness.